Dancing with dragons: Chinese import penetration and the performances of manufacturing firms in South Africa - Sofia Torreggiani; Antonio Andreoni (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2019)
Using firm-level tax administrative data from 2010 to 2017, we study the impact of Chinese import penetration on the performances of manufacturing firms in South Africa, and whether firms investing in capabilities development are more resilient to such competitive pressure. Specifically, by instrumenting Chinese import penetration with China's share in other low- and middle-income countries' imports, we first explore whether Chinese import exposure - both direct (e.g. affecting the sector in which the firm itself operates) and indirect (e.g. through input-output linkages along the domestic value chain) - have been associated with firms downsizing in terms of decreasing employment and sales growth and higher probability of exiting the market. Second, we examine whether firms investing in process and product innovation and skills development perform better in response to import competition. Our results indicate that rising Chinese import exposure - not only direct, but also in downstream segments of the domestic value chain - leads to slower sales and employment growth for the entire sample of surviving firms and to higher probability of shutdown for firms not undertaking any spending in capabilities development. However, we also find that the negative impact of Chinese import penetration is partially mitigated by investments in capital, innovation, and skills development.
Keywords: D22; F14; F61; F63; L25; 330; capabilities; Chinese import competition; direct and indirect import penetration; manufacturing; South Africa